2014
DOI: 10.1002/pon.3705
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in cancer patients within the first year of diagnosis

Abstract: Cancers with an advanced stage at diagnosis were associated with an increased risk of suicide within 1 year of diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 32 publications
3
73
1
5
Order By: Relevance
“…Most important, patients with cancer had dramatically increased risks of depression, anxiety, stress reaction/adjustment disorder, and substance abuse (excluding alcohol and tobacco abuse or dependence), as well as somatoform/conversion disorder, both during the year before and the year after diagnosis. The dramatic risk increases noted immediately after cancer diagnosis corroborate with previous findings on highly increased risks of cardiovascular diseases and suicide right after cancer diagnosis, [6][7][8][9][10][11][12] whereas the clearly elevated risks during the year before diagnosis may suggest the effect of prediagnostic cancer symptoms as well as the severe stress of undergoing clinical evaluation for a suspected malignancy. To a varying extent, there was a similar pattern of risk elevation for most cancer types, with the smallest (if any) risk increase observed for nonmelanoma skin cancer.…”
Section: Discussionsupporting
confidence: 79%
“…Most important, patients with cancer had dramatically increased risks of depression, anxiety, stress reaction/adjustment disorder, and substance abuse (excluding alcohol and tobacco abuse or dependence), as well as somatoform/conversion disorder, both during the year before and the year after diagnosis. The dramatic risk increases noted immediately after cancer diagnosis corroborate with previous findings on highly increased risks of cardiovascular diseases and suicide right after cancer diagnosis, [6][7][8][9][10][11][12] whereas the clearly elevated risks during the year before diagnosis may suggest the effect of prediagnostic cancer symptoms as well as the severe stress of undergoing clinical evaluation for a suspected malignancy. To a varying extent, there was a similar pattern of risk elevation for most cancer types, with the smallest (if any) risk increase observed for nonmelanoma skin cancer.…”
Section: Discussionsupporting
confidence: 79%
“…But SMR is observed to be higher within the first year of NSCLC diagnosis among patients diagnosed between 2004 and 2013. It has been reported that cancer patients were at high risk of suicide within the first year of diagnosis and associated demographic and clinical factors were analyzed 36. The different result can be possibly explained by the improvement of life quality of long‐term survivor of NSCLC patients, and the major reason for suicidal behavior of recent NSCLC patients is possibly shock of cancer diagnosis 37, 38…”
Section: Discussionmentioning
confidence: 99%
“…That observation is likely multifactorial and not merely a reflection of the poor prognosis associated with advanced stage, which has previously been shown to increase the likelihood of suicide 10,15,17,25 . The desire for hastened death in advanced and terminally ill cancer patients correlates with physical symptoms, quality of life, and the perception of being a burden to others 6 .…”
Section: Discussionmentioning
confidence: 99%